2018
DOI: 10.1002/cbic.201800275
|View full text |Cite
|
Sign up to set email alerts
|

Coordination‐Assisted Bioorthogonal Chemistry: Orthogonal Tetrazine Ligation with Vinylboronic Acid and a Strained Alkene

Abstract: Bioorthogonal chemistry can be used for the selective modification of biomolecules without interfering with any other functionality that might be present. Recent developments in the field include orthogonal bioorthogonal reactions to modify multiple biomolecules simultaneously. During our research, we observed that the reaction rates for the bioorthogonal inverse-electron-demand Diels-Alder (iEDDA) reactions between nonstrained vinylboronic acids (VBAs) and dipyridyl-s-tetrazines were exceptionally higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 38 publications
6
26
0
Order By: Relevance
“…This led to the development of potential two‐step ABPs 8 – 14 (Figure ) as strained, electron‐rich alkenes for bioorthogonal labeling using iEDDA as the ligation strategy. Compound 12 was included in the research of bioorthogonal iEDDA reactions between non‐strained vinylboronic acids and pyridyl‐substituted tetrazines …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the development of potential two‐step ABPs 8 – 14 (Figure ) as strained, electron‐rich alkenes for bioorthogonal labeling using iEDDA as the ligation strategy. Compound 12 was included in the research of bioorthogonal iEDDA reactions between non‐strained vinylboronic acids and pyridyl‐substituted tetrazines …”
Section: Resultsmentioning
confidence: 99%
“…In case the inhibitors are covalent and irreversible, they can be modified to contain reporter entities for activity‐based proteasome profiling purposes. Recently, we disclosed a set of inhibitors selective for one of each of the six catalytic subunits of human constitutive proteasomes and immunoproteasomes (Figure ), whereas activity‐based proteasome probes have also been reported by other research groups . With this set of subunit‐selective inhibitors 1 – 7 (Figure A), each human proteasome activity can be inhibited at will.…”
Section: Introductionmentioning
confidence: 99%
“…4,17 Such mutually orthogonal reagents are in demand for chemical tagging of multiple biomolecules. [5][6][7][8][9][10][11][12][13][14] We recently reported that a 6-substituted 1,2,4-triazine constitutes a new privileged scaffold (Fig. 1A).…”
mentioning
confidence: 99%
“…In fact, there are only a handful of bioorthogonal reaction pairs that can be used simultaneously. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] We are developing "privileged" scaffolds that not only meet the requirements for bioorthogonality, but are also compatible with existing reagents to enable tandem application. 4,17 Such mutually orthogonal reagents are in demand for chemical tagging of multiple biomolecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation